Silica aerogel grafted titanium dioxide nanodot dispersion and preparation method and application thereof
By grafting titanium dioxide nanodots on the surface of silica aerogel and preparing anatase nanodots by hydrothermal method, the problem in the prior art that silica aerogels are difficult to maintain high specific surface area and low thermal conductivity characteristics while imparting high photocatalytic performance, achieving efficient and low-temperature prepared silica aerogels loaded anatase nanodots.
Patent Information
- Application Number
- CN202310722362.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-06-19
AI Technical Summary
The prior art is difficult to maintain its high specific surface area and low thermal conductivity characteristics in a silica aerogel while imparting high photocatalytic properties of titanium dioxide, especially without high temperature heat treatment.
By first preparing a micron-scale silica aerogel paste, then grafting titanium dioxide nanodots on its surface, anatase-type titanium dioxide nanodots are prepared at a lower temperature by hydrothermal method, and bonding to the surface of the silica aerogel through Si-O-Ti bonds, the nanoporous structure and dispersion of the material are ensured.
It is achieved that the silicon dioxide aerogel-loaded anatase nanodots with high specific surface area and low thermal conductivity are prepared without destroying the original characteristics of the silica aerogel. It has high photocatalytic efficiency and is suitable for low-temperature preparation.
Smart Images

Figure CN117004267B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and in particular relates to a silicon dioxide aerogel grafted titanium dioxide nanodot dispersion and a preparation method and application thereof. Background Art
[0002] Titanium dioxide has the advantages of high chemical stability, high photoelectric conversion efficiency, high activity, non-toxicity, and low cost. It is widely used in photocatalysis, energy storage and conversion, biomedicine, information storage and other fields. Among them, titanium dioxide with excellent catalytic performance usually has the characteristics of anatase crystal form, small size (nanoscale), high specific surface area, and low electron-hole recombination rate, which can be achieved through doping, size nano-sizing, crystal form regulation, and composite methods. Because the refinement of titanium dioxide particles can effectively increase the specific surface area, that is, the active site, it has become an important research direction for the synthesis and preparation of materials, but its stability or recyclability faces huge challenges. Based on this, the researchers proposed a solution to optimize the comprehensive performance of materials by combining titanium dioxide with porous materials, and made great progress. The comprehensive improvement of performance achieved by the composite of titanium dioxide and silicon dioxide is a typical example.
[0003] In recent years, silica aerogel has developed rapidly due to its promotion and application in the fields of battery fire protection and heat insulation, industrial pipeline insulation, etc., and the multifunctionalization of its related products has also begun to become a hot research direction. The composite of titanium dioxide and silica aerogel is expected to give titanium dioxide excellent catalytic properties while maintaining the basic functions of silica aerogel, thereby expanding the application scenarios of silica aerogel. However, the thermal conductivity of titanium dioxide aerogel is higher than that of silica aerogel, and its specific surface area and porosity are lower than those of silica aerogel, and it usually needs to be heat treated at more than 500°C to have anatase crystal form with high photocatalytic performance. As mentioned in the patent "A TiO 2 / SiO 2 The XRD diagram in the patent "Preparation method and application of aerogel microspheres" shows that the prepared material is an amorphous structure rather than anatase. 2 / SiO 2 Composite aerogel and its application" prepared TiO 2 / SiO 2 Composite aerogel, but the crystal form and morphology of the prepared material are not clear. Based on the inventor's existing knowledge and previous research on TiO 2 The experience accumulated in the preparation of aerogels (preparation of TiO2 aerogel by atmospheric pressure drying method [J]. Journal of Composite Materials, (3) 2012, 127) shows that the current TiO2 aerogels that have not been heat treated can be 2Aerogels are mostly amorphous structures and require subsequent heat treatment to obtain anatase crystal materials. However, heat treatment at higher temperatures will cause the nanoporous structure to collapse and lose the thermal insulation properties of the aerogel. 2 / SiO 2 Preparation method of porous material", "a TiO 2 -SiO 2 Visible light photocatalytic composite film and preparation method thereof", "A nano-titanium dioxide / silicon dioxide aerogel modified polymer cement waterproof coating and preparation method thereof" etc. also require the sample to be heat treated at 550-800℃ or calcined in a muffle furnace to achieve excellent catalytic performance of the material. Therefore, it is difficult to obtain TiO2 with characteristic structures such as anatase, nano-size, and high specific surface area by using conventional aerogel preparation process without subsequent heat treatment. 2 / SiO 2 Composite aerogel.
[0004] Based on the above problems that need to be solved in the prior art, the present invention proposes to first prepare a micron-sized silica aerogel paste, and then graft titanium dioxide nanodots on its surface; while ensuring that the pore characteristics of the original silica aerogel are not destroyed, the present invention can diffusely graft an appropriate amount of titanium dioxide anatase nanodots on its particle surface; while solving the problem of easy agglomeration of nanodots, it can achieve low-temperature preparation of anatase with high catalytic efficiency. This helps to make full use of the excellent properties of silica aerogel and titanium dioxide, and expand the application range of silica aerogel, such as giving it a new function of air purification on the basis of existing silica aerogel coatings. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a silica aerogel grafted titanium dioxide nanodot dispersion and a preparation method and application thereof.
[0006] The first object of the present invention is to provide a silica aerogel-grafted titanium dioxide nanodot dispersion, and the technical scheme is as follows:
[0007] A silica aerogel-grafted titanium dioxide nanodot dispersion, wherein the dispersion comprises, by mass percentage:
[0008] 5-22% of silica aerogel grafted with titanium dioxide nanodots, 1-5% of a functional additive, and the remainder a solvent;
[0009] The titanium dioxide nanodots are perovskite-type;
[0010] The functional additive is one or more of nonionic polyoxyethylene modified polydimethylsiloxane, polyether modified polyorganosiloxane and hydroxy polyether modified polyorganosiloxane.
[0011] Furthermore, the particle size of the silica aerogel grafted with titanium dioxide nanodots is 3 to 25 μm.
[0012] Furthermore, the particle size of the titanium dioxide nanodots is 3 to 6 nm.
[0013] Furthermore, the specific surface area of the silica aerogel grafted with titanium dioxide nanodots is greater than 500 m 2 / g.
[0014] Furthermore, the mass percentage of titanium dioxide nanodots in the silicon dioxide aerogel grafted with titanium dioxide nanodots is 5 to 25%.
[0015] Furthermore, the solvent is a mixture of one or more of water, ethylene glycol and propylene glycol.
[0016] The second object of the present invention is to provide a method for preparing the above-mentioned silica aerogel grafted titanium dioxide nanodot dispersion, and the technical scheme is as follows:
[0017] The method for preparing a dispersion of silica aerogel grafted with titanium dioxide nanodots comprises the following steps:
[0018] (1) Preparation of aqueous silica aerogel dispersion: water and functional additives are mixed uniformly in proportion, and then hydrophobic silica aerogel powder is added. Under a vacuum degree of 0.06 to 0.08 MPa, the mixture is stirred at a high speed of 1500 to 2000 rpm for 1 to 2 hours to obtain a silica aerogel dispersion.
[0019] (2) adding the silica aerogel dispersion, alcohol solvent, acid catalyst and titanium source of step (1) into a hydrothermal reactor in proportion to carry out a hydrothermal reaction, and obtaining a mixture after the hydrothermal reaction is completed;
[0020] (3) The mixture is mixed with water and then filtered to obtain a dispersion of silica aerogel grafted titanium dioxide nanodots.
[0021] Furthermore, the contact angle between the hydrophobic silica aerogel powder and water is greater than 120°.
[0022] Furthermore, the mass ratio of the water, the functional additive and the silica aerogel powder is 1-5:75-85:14-20.
[0023] Furthermore, the mass ratio of the silica aerogel dispersion, the alcohol solvent, the acid catalyst and the titanium source is 1:1-12:0.4-4:0.2-2.
[0024] Furthermore, the alcohol solvent is ethylene glycol, propylene glycol or a mixture of the two.
[0025] Furthermore, the acid catalyst is one or more of hydrochloric acid, sulfuric acid, nitric acid, histidine, and citric acid.
[0026] Furthermore, the titanium source is one or both of tetrabutyl titanate and titanium tetrachloride.
[0027] Furthermore, the temperature of the hydrothermal reaction is 100-180° C., the time of the hydrothermal reaction is 2-16 hours, and mechanical stirring is performed during the hydrothermal reaction, and the rotation speed of the mechanical stirring is 200-600 r / min.
[0028] Furthermore, the weight ratio of the mixture to water is 1:2-5.
[0029] The third object of the present invention is to provide the use of the above-mentioned silica aerogel grafted titanium dioxide nanodot dispersion as an additive in coatings.
[0030] Furthermore, the coating is a water-based acrylic coating.
[0031] The beneficial effects of the present invention are:
[0032] (1) The silica aerogel grafted titanium dioxide nanodot dispersion of the present invention has both the high specific surface area and low thermal conductivity characteristics of silica aerogel and the high photocatalytic properties of anatase titanium dioxide nanodots, and can be used as an additive in interior wall coatings, and has the function of degrading organic pollutants such as formaldehyde.
[0033] (2) In the process of preparing silica aerogel loaded with anatase nanodots by the hydrothermal method of the present invention, the alcohol solvent can adhere to the surface of the silica aerogel powder without entering the internal hydrophobic nanopores, thereby ensuring the integrity of the aerogel structure and providing raw materials for the hydrothermal reaction, thereby promoting the nucleation and growth of anatase nanodots on the surface of the silica aerogel.
[0034] (3) The addition of acid in the preparation method of the present invention can alleviate the condensation process of the hydrothermal reaction precursor, help prepare fine nanodots, and increase the time window of the material in the industrial preparation process.
[0035] (4) The present invention can ensure the preparation of anatase titanium dioxide by selecting a lower acid / titanium source ratio and a suitable hydrothermal temperature without destroying the original nanoporous structure of the silica aerogel particles.
[0036] (5) The titanium dioxide nanodots of the present invention are bonded to the surface of the silica aerogel micron powder through Si-O-Ti bonds, so that the hydrophilicity of the surface of the silica aerogel powder is improved, while the hydrophobicity of the interior remains unchanged, thereby retaining the nanoporous structure and uniform dispersion characteristics in the dispersion, which not only overcomes the problem of easy agglomeration of the nanodots, but also helps to separate the photogenerated electron-hole pairs, thereby realizing the low-temperature preparation of silica aerogel-loaded anatase nanodots with high specific surface area and high catalytic efficiency.
[0037] (6) The preparation method of the present invention is simple and practical, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The high-resolution transmission electron microscopy image (a) and the high-resolution Fourier transform image (b) of the silica aerogel grafted with titanium dioxide nanodots of Example 1 of the present invention;
[0039] Figure 2 This is the FT-IR image of the silica aerogel grafted with titanium dioxide nanodots in Example 1 of the present invention;
[0040] Figure 3 This is a diagram of the photocatalytic degradation of methyl blue by the silica aerogel grafted with titanium dioxide nanodots according to Example 1 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0042] Example 1
[0043] (1)SiO 2 Preparation of aerogel powder dispersion:
[0044] 5% (mass percentage) of polyether-modified polyorganosiloxane (functional additive) was mixed with 75% (mass percentage) of deionized water, stirred at a low speed of 300 rpm, and then 20% (mass percentage) of SiO 2 Aerogel powder (the particle size of aerogel powder is 3-10 μm) was stirred at high speed in vacuum at a speed of 2000 rpm, a vacuum degree of 0.06 MPa, and a stirring time of 1 hour to obtain SiO 2 Aerogel dispersions.
[0045] (2) Hydrothermal reaction:
[0046] The SiO 2Aerogel dispersion, ethylene glycol, hydrochloric acid, and tetrabutyl titanate were added to the hydrothermal reactor in a proportion of 1:7:3:0.7, mixed evenly, and subjected to hydrothermal reaction for 12 hours at a temperature of 150°C. Mechanical stirring was performed at a speed of 200 r / min during the hydrothermal reaction.
[0047] (3) Filtration and washing
[0048] The mixture of step (2) and water were mixed evenly in a weight ratio of 1:5, and filtered to obtain SiO 2 Aerogel grafted TiO 2 Nanodot dispersion.
[0049] Figure 1 The SiO 2 Aerogel grafted TiO 2 High-resolution transmission electron microscopy of nanodots Figure 1 (a) and high-resolution Fourier transform Figure 1 (b) Figure 1 (a) It can be seen that SiO 2 TiO grafted on the surface of aerogel 2 The size of the nanodots is about 5nm, and the crystal form is anatase; Figure 1 (b) High-resolution TEM Fourier transform image shows that the prepared TiO 2 It is anatase nanocrystal.
[0050] Figure 2 The SiO 2 Aerogel grafted TiO 2 FT-IR image of nanodots. It can be seen from the figure that SiO 2 Aerogel and TiO 2 The nanodots are connected by chemical bonding, that is, at 910 cm -1 The Ti-O-Si bond peak appears at around 2.1 wavenumber.
[0051] Figure 3 The SiO 2 Aerogel grafted TiO 2 The decomposition rate of nanodots on methylene blue aqueous solution. The experiment used 100ml 10mg / L methylene blue solution (PH=5.5), 5mg sample and 3kW / m 2 The simulated sunlight conditions. As shown in the figure, the residual concentration of methyl blue (C / C 0 ) is lower than 40%, indicating that the material has excellent catalytic decomposition efficiency.
[0052] Comparative Example 1
[0053] The difference from Example 1 is that the mass percentage of the polyether-modified polyorganosiloxane is 0.5% (less than 1%), and after high-speed vacuum stirring at a speed of 2000 rpm and a vacuum degree of 0.06 MPa for 48 hours, no aerogel dispersion with a fluid form can be obtained. 2 The aerogel surface has a large contact angle, TiO 2 Nanodots cannot be formed on SiO 2 Aerogel surface bonding growth.
[0054] Comparative Example 2
[0055] The difference from Example 1 is that no hydrochloric acid is added. During the hydrothermal reaction, TiO 2 In SiO 2 The aerogel surface grows rapidly, and the size is micrometer-level, far larger than 10nm, and loses the nano-effect performance. After 48h, the residual concentration of methyl blue is c / c 0 The catalytic decomposition efficiency is greatly reduced.
[0056] Comparative Example 3
[0057] The difference from Example 1 is that the amount of hydrochloric acid is higher, SiO 2 The mass ratio of aerogel dispersion, ethylene glycol, hydrochloric acid, and tetrabutyl titanate is 1:7:6:0.2 (i.e., the mass ratio of hydrochloric acid to tetrabutyl titanate is greater than 4:0.2). At this time, after the hydrothermal reaction lasts for 96 hours, no aerogel can be formed on the SiO 2 TiO grafted onto aerogel surface 2 Nanodots indicate that when the amount of hydrochloric acid is too high, the nucleation and growth of tetrabutyl titanate after reduction is inhibited, affecting the production efficiency.
[0058] Comparative Example 4
[0059] The difference from Example 1 is that the amount of ethylene glycol is higher, SiO 2 The mass ratio of aerogel dispersion, ethylene glycol, hydrochloric acid, and tetrabutyl titanate is 1:120:3:1 (i.e., the mass ratio of ethylene glycol to tetrabutyl titanate>60:1). At this time, after the hydrothermal reaction lasts for 96 hours, no aerogel can be formed on SiO 2 TiO grafted onto aerogel surface 2 Nano dots. This indicates that when the amount of solvent ethylene glycol is too high, the concentration of tetrabutyl titanate decreases, the rate of hydrothermal reduction reaction decreases, and the nucleation and growth rate is greatly reduced, affecting production efficiency.
[0060] Comparative Example 5
[0061] The difference from Example 1 is that the filtration step is not performed, and the SiO 2 Aerogel grafted TiO2 The nanodot dispersion is doped with TiO 2 Nanoparticles.
[0062] Example 2
[0063] (1)SiO 2 Preparation of aerogel powder dispersion:
[0064] 1% (mass percentage) of polyether-modified polyorganosiloxane (functional additive) was mixed with 85% (mass percentage) of deionized water, stirred at a low speed of 300 rpm, and then 14% (mass percentage) of SiO 2 Aerogel powder (the particle size of aerogel powder is 10-25 μm) was stirred at high speed in vacuum at a speed of 1500 rpm, a vacuum degree of 0.08 MPa, and a stirring time of 1 hour to obtain SiO 2 Aerogel dispersions.
[0065] (2) Hydrothermal reaction:
[0066] The SiO 2 Aerogel dispersion, propylene glycol, citric acid, and titanium tetrachloride were added to the hydrothermal reactor in a proportion of 1:12:4:0.2, mixed evenly, and subjected to hydrothermal reaction for 16 hours at a temperature of 180°C. Mechanical stirring was performed at a speed of 600 r / min during the hydrothermal reaction.
[0067] (3) Filtration and washing
[0068] The mixture of step (2) and water were mixed evenly in a weight ratio of 1:2, and filtered to obtain SiO 2 Aerogel grafted TiO 2 Nanodot dispersion.
[0069] Example 3
[0070] Preparation method of multifunctional coating for interior wall thermal insulation and formaldehyde degradation
[0071] 28% of water-based acrylic resin (BASF 502 in this embodiment) and 34% of SiO 2 Aerogel grafted TiO 2Nanodot dispersion, 10% hollow glass microspheres (D90 is 60 μm), 0.1% unsaturated alkane defoamer (BYK-A500 is selected in this embodiment), 0.1% hydrophobically modified alkali swellable acrylic emulsion thickener (Dow TT-935 is selected in this embodiment), 0.05% by weight of 1,2-benzisothiazolin-3-one bactericide and the rest of water are mixed evenly at a low speed of 800 rpm and a stirring time of 1 hour to obtain a multifunctional coating for interior wall thermal insulation and formaldehyde degradation.
[0072] The performance indicators of the multifunctional coating for interior wall thermal insulation and formaldehyde degradation prepared in this embodiment are shown in Table 1 below.
[0073] Table 1 Performance indicators of the interior wall thermal insulation and formaldehyde degradation multifunctional coating of Example 3
[0074]
[0075]
[0076] According to the JC / T1074-2008 standard, two 1m 3 The glass test cabins were compared in parallel, keeping the temperature, humidity, glass cabin adsorption, cabin air leakage and other factors constant. The blank experiment and sample test were performed according to the formaldehyde sampling and analysis method in the "Method for Determination of Formaldehyde in Air in Public Places" B / T18204.26-2000. After drawing the blank baselines of the two parallel cabins based on multiple sets of experimental data, it was found that the relative error of the blank experimental values of the two cabins was small, and the "parallel" performance was truly achieved. At the same time, the performance of the coating (thickness of 1mm) in Example 3 for purifying formaldehyde was tested and evaluated with the L cabin as the sample test cabin and the R cabin as the blank test cabin (at 3kW / m 2 The results showed that after 3 hours, the formaldehyde content in the L cabin coated with Example 3 was 35% of that in the R cabin, and the formaldehyde adsorption and decomposition performance was significant.
[0077] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A silica aerogel grafted titanium dioxide nanodot dispersion, characterized in that: The dispersion comprises, by mass percentage: 5-22% of silica aerogel grafted with titanium dioxide nanodots, 1-5% of functional additives, and the balance of solvent; The titanium dioxide nanodots are perovskite-type; The functional additive is one or more of nonionic polyoxyethylene modified polydimethylsiloxane, polyether modified polyorganosiloxane, and hydroxy polyether modified polyorganosiloxane; The preparation method of the dispersion comprises the following steps: (1) Preparation of aqueous silica aerogel dispersion: water and functional additives are mixed uniformly in proportion, and then hydrophobic silica aerogel powder is added. Under a vacuum degree of 0.06-0.08 MPa, the mixture is stirred at a high speed of 1500-2000 rpm for 1-2 hours to obtain a silica aerogel dispersion, wherein the mass ratio of water, functional additive, and silica aerogel powder is 1-5:75-85:14-20; (2) adding the silica aerogel dispersion, alcohol solvent, acid catalyst and titanium source of step (1) into a hydrothermal reactor in proportion to carry out a hydrothermal reaction, and obtaining a mixture after the hydrothermal reaction, wherein the mass ratio of the silica aerogel dispersion, alcohol solvent, acid catalyst and titanium source is 1:1-12:0.4-4:0.2-2, and the weight ratio of the mixture to water is 1:2-5; (3) The mixture is mixed with water and then filtered to obtain a dispersion of silica aerogel grafted titanium dioxide nanodots.
2. The silica aerogel-grafted titanium dioxide nanodot dispersion according to claim 1, characterized in that: The silica aerogel grafted with titanium dioxide nanodots has a particle size of 3 to 25 μm and a specific surface area of more than 500 m 2 / g; the particle size of the titanium dioxide nanodots is 3~6nm.
3. The silica aerogel-grafted titanium dioxide nanodot dispersion according to claim 1, characterized in that: The mass percentage of titanium dioxide nanodots in the silicon dioxide aerogel grafted with titanium dioxide nanodots is 5-25%.
4. The silica aerogel-grafted titanium dioxide nanodot dispersion according to claim 1, characterized in that: The solvent is one or a mixture of water, ethylene glycol and propylene glycol.
5. A preparation method for preparing the silica aerogel-grafted titanium dioxide nanodot dispersion according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of aqueous silica aerogel dispersion: water and functional additives are mixed evenly in proportion, and then hydrophobic silica aerogel powder is added. Under vacuum conditions of 0.06-0.08 MPa, the silica aerogel dispersion is obtained after high-speed stirring at 1500-2000 rpm for 1-2 hours. (2) adding the silica aerogel dispersion, alcohol solvent, acid catalyst and titanium source prepared in step (1) into a hydrothermal reactor in proportion to carry out a hydrothermal reaction, and obtaining a mixture after the hydrothermal reaction is completed; (3) The mixture is mixed with water and then filtered to obtain a dispersion of silica aerogel grafted titanium dioxide nanodots.
6. The preparation method according to claim 5, characterized in that: The contact angle between the hydrophobic silica aerogel powder and water is greater than 120°.
7. The preparation method according to claim 5, characterized in that The mass ratio of the water, the functional additive and the silica aerogel powder is 1-5: 75-85: 14-20; the mass ratio of the silica aerogel dispersion, the alcohol solvent, the acid catalyst and the titanium source is 1: 1-12: 0.4-4: 0.2-2; and the weight ratio of the mixture and water is 1: 2-5.
8. The preparation method according to claim 5, characterized in that: The alcohol solvent is one of ethylene glycol and propylene glycol or a mixture of the two; the acid catalyst is one or more of hydrochloric acid, sulfuric acid, nitric acid, histidine and citric acid; the titanium source is one of tetrabutyl titanate and titanium tetrachloride or both.
9. The preparation method according to claim 5, characterized in that: The temperature of the hydrothermal reaction is 100-180° C., the time of the hydrothermal reaction is 2-16 hours, and mechanical stirring is performed during the hydrothermal reaction, and the rotation speed of the mechanical stirring is 200-600 r / min.
10. Application of a silica aerogel grafted titanium dioxide nanodot dispersion in coatings, characterized in that: The silica aerogel grafted titanium dioxide nanodot dispersion described in any one of claims 1 to 4 or the silica aerogel grafted titanium dioxide nanodot dispersion prepared by the preparation method described in any one of claims 5 to 9 is used as an additive.
Citation Information
Patent Citations
Nano-titanium dioxide / silicon dioxide aerogel modified polymer cement waterproof coating and preparation method thereof
CN107446450A
Preparation method of silicon-titanium aerogel adsorption and photocatalytic inner wall coating
CN108410366A